The effect of different formulations of milkfish (Chanos chanos) bone flour and nile tilapia (Oreochromis niloticus) bone flour on the physical, chemical, and organoleptic properties of milkfish nuggets - Hidayah, Nurul; Nasution, Puterie Akila Bijakin (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
Indonesia possesses abundant natural resources in fisheries commodities; however, the level of fish consumption among the Indonesian population remains relatively low. Product innovation in processed foods, such as fish nuggets, can serve as a strategy to increase the added value of fish while also utilizing fisheries by-products, particularly fish bones, which are rich in calcium. This study aimed to determine the effect of different formulations of milkfish (Chanos chanos) bone flour and Nile tilapia (Oreochromis niloticus) bone flour on the physical, chemical, and organoleptic properties of milkfish nuggets. The research was conducted using a Completely Randomized Design (CRD) with five different formulations based on varying ratios of milkfish bone flour and Nile tilapia bone flour, namely A0 (100:0), A1 (75:25), A2 (50:50), A3 (25:75), and A4 (0:100). The evaluated parameters included physical analysis, chemical analysis (moisture, ash, fat, protein, and calcium content), and organoleptic evaluation (descriptive and hedonic tests). The results indicated that differences in the formulation of milkfish bone flour and Nile tilapia bone flour in milkfish nuggets had a significant effect (p < 0.05) on hardness, crunchiness, gumminess, protein content, and calcium content. The A0 formulation produced the highest calcium content at 852.89 ± 10.34 mg/100 g, while A2 showed the highest protein content at 12.93 ± 0.00%. Organoleptically, the A2 formulation was superior in color and taste attributes, A4 in aroma and aftertaste, while A0 in texture.